Endovascular treatment of a middle cerebral artery bifurcation aneurysm - Rosales Bravo, Luis Manuel (2013)
Cerebral aneurysms of the middle cerebral artery are a frequent cause of spontaneous subarachnoid hemorrhage. The surgical neck clipping-to prevent rebleeding-has traditionally been the treatment of choice. Currently depending on the morphology of the aneurysm sac, the ratio neck / dome and the absence of arterial branches that arise from the aneurysm sac, make possible the endovascular treatment of aneurysms using coils.This technique achieves complete exclusion of the aneurysm from the cerebral blood flow with a low rate of recanalization and complications. The goal of treatment is to exclude the aneurysm from the cerebral circulation preventing the rebleeding, reduce he risk of thromboembolic complications and reduce mortality in this patient ́s group. Through a clinical case is showed an endovascular treatment of a ruptured sacular middle cerebral artery bifurcation neurysm. In the Costa Rica ́s medical literature this is the firt reported case